2017
DOI: 10.1128/aem.03250-16
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Colonization and Transmission in the Burying Beetle Nicrophorus vespilloides throughout Development

Abstract: Carrion beetles in the genus Nicrophorus rear their offspring on decomposing carcasses where larvae are exposed to a diverse community of decomposer bacteria. Parents coat the carcass with antimicrobial secretions prior to egg hatch (defined as prehatch care) and also feed regurgitated food, and potentially bacteria, to larvae throughout development (defined as full care). Here, we partition the roles of prehatch and posthatch parental care in the transmission and persistence of culturable symbiotic bacteria t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 60 publications
(108 reference statements)
4
80
0
Order By: Relevance
“…Interestingly, Wohlfahrtiimonas and Morganella morganii , both detected in N. vespilloides guts in this study, were previously found to be resistant to the antibiotics produced by Myroides (Dharne et al., ), indicating that the N. vespilloides microbiota may be shaped by organisms that have evolved resistance against the antimicrobial action of other bacterial members constituting its core microbiome. Vagococcus , Myroides , Providencia and Morganella have also been detected in culture‐dependent studies (Wang & Rozen, ) to be transmitted by N. vespilloides adults to their larvae. Given their prevalence in meat (either fresh or decomposing) and in the gut of flesh‐feeding insects, and their diverse digestive and antimicrobial properties, these bacteria could play important roles in carcass digestion and preservation.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Wohlfahrtiimonas and Morganella morganii , both detected in N. vespilloides guts in this study, were previously found to be resistant to the antibiotics produced by Myroides (Dharne et al., ), indicating that the N. vespilloides microbiota may be shaped by organisms that have evolved resistance against the antimicrobial action of other bacterial members constituting its core microbiome. Vagococcus , Myroides , Providencia and Morganella have also been detected in culture‐dependent studies (Wang & Rozen, ) to be transmitted by N. vespilloides adults to their larvae. Given their prevalence in meat (either fresh or decomposing) and in the gut of flesh‐feeding insects, and their diverse digestive and antimicrobial properties, these bacteria could play important roles in carcass digestion and preservation.…”
Section: Discussionmentioning
confidence: 95%
“…Nicrophorus larvae are exposed to a highly diverse microbiota in their breeding environment, first from the soil where they hatch and next from the microbes proliferating on and within their carrion resource. In the absence of parental care, larvae become colonized with these bacteria (Wang & Rozen, ) which reduces their weight and survival (Rozen et al., ) and also leads to reduced brood mass when these larvae reproduce as parents (Figure ). However, when larvae are reared with parental care, their gut microbiome resembles that of their parent, even if parental care is limited to carcass preparation prior to larval hatch (Wang & Rozen, ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if “endogenous” bacteria can outcompete foreign strains during larval colonization, we competed bacterial strains against one another within the larval gut, focusing on four different bacterial species. The bacterial species Providencia rettgeri and Morganella morganii are abundant N. vespilloides gut symbionts throughout development and are considered “endogenous” species (Vogel et al., ; Wang & Rozen, ). By contrast, S. marcescens and Escherichia coli , which are found commonly in both soil and on decomposing carcasses, colonize larvae that are reared without parental care in NC broods (Wang & Rozen, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations